2015
DOI: 10.1088/1757-899x/88/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation to study effect of radiation on thermal performance of radiator for onan cooling configuration of transformer

Abstract: Abstract. In the present work, flow and temperature distribution in the radiator fins of a power transformer is studied numerically with conjugate heat transfer using commercial CFD software to study the effect of radiation on heat dissipation. The approach considered here is a complete 3D geometry of the radiator fins with average height of the flute geometry of the fins for meshing and computational time reduction. Simulations are performed for ONAN (Oil Natural Air Natural) case for one radiator configurati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The convection exists in both the internal insulating oil and the external cooling air. The radiation can mostly be found on the outwards facing surfaces, as discovered in [11]. All three mechanisms and the cooling media are considered and included in the full radiator CFD model.…”
Section: B Full Cfd Model Including Air Domainmentioning
confidence: 99%
“…The convection exists in both the internal insulating oil and the external cooling air. The radiation can mostly be found on the outwards facing surfaces, as discovered in [11]. All three mechanisms and the cooling media are considered and included in the full radiator CFD model.…”
Section: B Full Cfd Model Including Air Domainmentioning
confidence: 99%
“…As a result, optimization was obtained: reducing the cooling elements and their size, reconfiguring the design, changing the dimensions of the oil tank, and optimal location of the front and rear radiators on the oil tank. Chandak et al, [17] conducted a CFD analysis to investigate the effect of radiation on transformer coolant heat dissipation. Close inspection provides the possibility of increased heat dissipation even with the central coolant fins.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the study introduced a methodology to estimate airflow velocity by considering the fan properties and radiator structure in thermal calculations. In their study, Chandak et al [19] conducted a numerical analysis to investigate the impact of radiation on the transfer of heat from a transformer radiator. The researchers observed that a consideration of radiation is necessary when examining the natural convection scenario.…”
Section: Introductionmentioning
confidence: 99%